2020
DOI: 10.1021/acsami.0c12532
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Doped BaCeO3–BaZrO3 as a Chemically Stable Electrolyte with High Proton-Conductivity for Intermediate Temperature Solid Oxide Electrolysis Cells (SOECs)

Abstract: Solid oxide electrolysis cells (SOECs) are devices that enable economically viable production of clean fuel such as hydrogen gas, which can be used in many industrial applications and serving as an energy carrier for renewable energy sources. Operation of SOEC at intermediate temperature (IT) range (400 to 600 °C) is highly attractive because many unexploited heat sources from industries can be utilized. Proton conducting SOECs based on barium− zirconium−cerate electrolytes show great potential for operating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 48 publications
(77 reference statements)
0
40
0
Order By: Relevance
“…For example, Rajendran et al reported a tri-doped BaCeO 3 -BaZrO 3 by partially substituting Zr with Y, Yb, and gadolinium (Gd), forming BaCe 0.5 Zr 0.2 Y 0.1 Yb 0.1 Gd 0.1 O 3−δ (BCZYYbGd). 44 XRD spectra showed that the BCZYYbGd electrolyte was stable over 200 hours at 50 vol % steam in argon and 600°C (Figure 5D). This was attributed to the higher electronegativity value of Gd (1.20) compared to that of the host Ce (1.12), which stabilizes the crystal structure and minimizes the dopant−hydroxyl interaction.…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations
“…For example, Rajendran et al reported a tri-doped BaCeO 3 -BaZrO 3 by partially substituting Zr with Y, Yb, and gadolinium (Gd), forming BaCe 0.5 Zr 0.2 Y 0.1 Yb 0.1 Gd 0.1 O 3−δ (BCZYYbGd). 44 XRD spectra showed that the BCZYYbGd electrolyte was stable over 200 hours at 50 vol % steam in argon and 600°C (Figure 5D). This was attributed to the higher electronegativity value of Gd (1.20) compared to that of the host Ce (1.12), which stabilizes the crystal structure and minimizes the dopant−hydroxyl interaction.…”
Section: F I G U R Ementioning
confidence: 99%
“…(D) XRD patterns of the BCZYYbGd film before and after exposure to 50 vol.% steam in argon at 600°C for 200 h. Reprinted with permission from Ref. 44 Copyright 2020 American Chemical Society. (E) The current density of the BCZYYC2 cell as a function of time tested at 700°C with a pulse voltage.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…To operate solid oxide cells at intermediate temperatures, materials with high ionic conductivity and low electronic conductivity are needed for the electrolyte layer. Certain proton-conducting oxides offer higher ionic conductivity than the best oxide ion conductors (acceptor-stabilized ZrO 2 , acceptor-doped CeO 2 , and Sr- and Mg-codoped LaGaO 3 ) and so can operate at lower temperatures with the same Ohmic resistance for an equivalent electrolyte geometry. Additionally, electrolysis cells using proton-conducting electrolytes generate H 2 at the fuel electrode that is undiluted with H 2 O, and proton conductors are also under development for gas separation and electrochemical reactors. Among proton conductors, the Y-doped BaZrO 3 –BaCeO 3 solid solution has received significant attention.…”
Section: Introductionmentioning
confidence: 99%